The portrait of teaching English in primary school under Kurikulum Merdeka: Teachers' voices - Irfan Fajrul Falah; Rita Kusumah; Yanuarti Apsari; Agatha Kristi Pramudika Sari (Concept : Community Concern for English Pedagogy and Teaching, 2023)
The changes in the national curriculum in Indonesia have been regular since independence day. It is an action taken to improve the quality of education given the demands of both the era and society, as well as to prepare for more competitive outcomes. This study concerns teachers' perceptions of the current curriculum (Kurikulum Merdeka). It is important to see how it is going in the practical field, particularly in teaching English in primary schools. Six English teachers from six different schools in Indonesia took part as participants in the current study. They were interviewed in two modes, onsite and online, to share their views regarding the Merdeka curriculum implementation. The result shows that both schools and policymakers have done several things regarding implementation. Meanwhile, along with its implementation, challenges exist, including time allotment, students’ proficiency, and students' motivation. Therefore, the findings should be taken seriously to improve the quality of teaching English at the primary level. Keywords: English; primary school;  Kurikulum Merdeka; policy